Situation in the Republic of Côte d'Ivoire, case of the Office of the Prosecutor c. Laurent Gbagbo, decision of Pre-Trial Chamber I hearing on the confirmation of the charges according to the article 61 (7) (c) ( i ) of the Rome Statute, on 3 june 2013 (2014)
Este documento contiene en texto completo el articulo Situación en la República de Costa de Marfil, caso de la Fiscalía c . Laurent Gbagbo, decisión de la Sala de Cuestiones Preliminares I sobre la audiencia de confirmación de cargos en relación con artículo 61 (7) ( c ) ( i ) del Estatuto de Roma publicado en Anuario Iberoamericano de Derecho Internacional Penal; Vol. 2; 153-157;Iberoamerican Yearbook of International Criminal Law; Vol. 2; 153-157;Anuário Iberoamericano de Direito Internacional Penal; Vol. 2; 153-157;2346-3120;10.12804/anidip02.01.2014